حصر إقامة الحدود في الإمام: دراسة فقهية: Implementing Hudud to the Imam: A Jurisprudential Study - Abdullah Rjoob, Hamza Jadullah; Mohamd Stete, Mohannad Foud (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
ملخص البحث يهدف البحث إلى دراسة حكم حصر إقامة الحدود في الإمام، وبيان مدى ومعنى ارتباط إقامة الحدود به وبوجوده، وبيان حكم إقامة الحدود حال عدمه، وذكر شرط هذه الإقامة، وقد اعتمد البحث المنهج التحليلي، مع الإفادة من المنهجين الاستقرائي والوصفي، وَفق إجراءات البحث العلمي في التوثيق والكتابة، وتوصل البحث إلى أن إقامة الحدود حال وجود الإمام المقيم لها تخت به، ويعزر من افتات عليه، وأن معنى الشوكة والمنعة وتحمل تبعات إقامة الحدود من أبرز المعاني التي ينبني عليها حكم إقامة الحدود، وأن إقامة قاضي الخوارج والبغاة للحدود واجب ما أمكن، وأن إقامة الحدود حال عدم الإمام جائزة ما لم تفض إلى مفسدة أكبر، وخلص إلى أن حصر إقامة الحدود في الإمام ليس حصرًا مطلقًا، وإنما هو حصر ينبني على نظرة مصلحية، فكان هذا الحصر متعلقًا بحال وجود الإمام لا حال عدمه، مع تعلق هذا الحصر حال وجوده وحال عدمه بالقوة والمنعة وتحمل تبعات الجناة، ما يجعل هذه الإقامة تجوز لغير الإمام حال عدمه بضوابط شديدة. ABSTRACT This study examines the ruling on restricting the implementation of hudud punishments to the Imam, clarifies the meaning and extent of their connection to his presence, and addresses the ruling and conditions of implementing hudud in his absence. Using an analytical approach supported by inductive and descriptive methods, the research concludes that when an Imam is present and capable, the enforcement of hudud is his exclusive authority, and any usurpation of this role warrants discretionary punishment. It further finds that effective power, authority, and the ability to bear the consequences of enforcement are central to determining this ruling. The study holds that the implementation of hudud in the absence of the Imam is permissible provided it does not lead to greater harm, and concludes that restricting hudud to the Imam is not absolute but based on considerations of public interest, allowing their enforcement by others in his absence under strict conditions.